Meydandan Geçme Cemi' In Takhtadjy Society And Pre-Islam Belief Motifs In This Cem - Çıblak Coşkun, Nilgün (Journal of Alevism-Bektashism Studies, 2010)
In this article, 'meydandan geçme cemi' is studied. This cem has an important place among Takhdajis which is an Alevi-Turkmen group, and during this cem accounted ones (musahipli olanlar) and avowed mar- ried couples (ikrar vermiş evli çiftler) are questioned in front of the dede and the society once in a year. The reason for the arrangement of the cem and the way it is carried out are initially explained, and then the pre- Islam beliefs and practices in this cam are determined. As a result of our analysis it has been observed that 'meydandan geçme cemi' has important functions such as achieving clear conscious by providing unity and cooperation in society. Moreover, it has been noted that there are great similarities between the practices in this cem and pre-Islam archaic Turkish beliefs.
Keywords: keyword